2020
DOI: 10.1186/s43055-020-00316-w
|View full text |Cite
|
Sign up to set email alerts
|

Detection of additional primary malignant tumor in cancer survivors: the use of PET/CT for image-guided biopsy

Abstract: Background PET/CT is a well-established tool in the diagnostic workup of oncology patients. With the advance in diagnosis and therapy of oncology patients, survivors are at risk of developing additional malignancies. This study aimed to evaluate the yield of 18F-FDG PET/CT in biopsy guidance for the detection of unexpected additional primary malignancies in patients with known primary cancers. Medical records of patients underwent 18F-FDG PET/CT scans from July 2015 to December 2017 were reviewed, and 644 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Shaban and Saleh investigated the rate of second primary malignancies on PET/CT imaging for patients with a known primary malignancy. They found that 4.67% of PET/CT scans had findings suggestive of a second primary, with a false positive rate of 31% 21 . Given the potential delay in treatment for the primary lesion, additional studies comparing cost and time to treatment should be conducted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shaban and Saleh investigated the rate of second primary malignancies on PET/CT imaging for patients with a known primary malignancy. They found that 4.67% of PET/CT scans had findings suggestive of a second primary, with a false positive rate of 31% 21 . Given the potential delay in treatment for the primary lesion, additional studies comparing cost and time to treatment should be conducted.…”
Section: Discussionmentioning
confidence: 99%
“…They found that 4.67% of PET/CT scans had findings suggestive of a second primary, with a false positive rate of 31%. 21 Given the potential delay in treatment for the primary lesion, additional studies comparing cost and time to treatment should be conducted. Clinicians must carefully balance the workup of incidental findings while simultaneously preparing the patient for treatment of their primary lesion.…”
Section: Discussionmentioning
confidence: 99%